A genderwise comparison of sleep habits of a sample adult population of Kathmandu - Gorkhali, Binu (Journal of Physiological Society of Nepal, 2020)
Introduction: A consolidated sleep of 7-9 hours has recuperative effect and improves cognitive function. Relating to their differences in sociodemograpic roles and physiological responses, men and women have different sleep characteristics. Gender differences in Nepalese population has not been reported. The knowledge could be helpful in addressing their sleep disorders.Materials and methods: Sleep-related information was collected by means of questionnaires from randomly selected adults visiting a blood donation center in Kathmandu.Results: Complete response was obtained from 442 participants - 317 males and 125 females, with comparable mean age. Most (83.26%) participants had 7-9 hours of sleep. Women went to bed earlier (9.43 pm ±57 min vs 10.05 pm ±77 min in men, p=0.006) as well as woke up earlier (5.37 am ±48 min vs 6.04 am ±91 min in men, p